Major Problems and Challenges of Egg Production and Marketing in Bangladesh - Md. Shahidu l Haque Bir (Journal of Agriculture, Food and Environment, 2020)
Currently poultry sector is one of the most promising sectors for Bangladesh. This sector can provide various opportunities to increase our national GDP. Ma-jor concerns of the study were focusing on the entire problems of the poultry sector.Data were collected from 19 reputed layer farms owner and 48 egg trad-ers located in two Upazila at Mymensingh district. In this study, some problems were considering such as major marketing problems were economic problems, lack of information system, improper supply of medicine and vaccines, lack of adequate and suitable transportation system and price instability. The study also evaluates some specific measures to minimize the existing problems in the poul-try sector and they are as government interfere in capital, providing right infor-mation of layer farming system, provision of adequate supply of medicine and veterinary services, development of transportation system, price stability by market monitoring. Combined with helpful government policies like extension of subsidies to layer farm owners will help Bangladesh to play a significant role in layer products trade besides meeting the ever increasing domestic demand. Results suggested that to increase layer production and develop the layer indus-try, the government as well as other private integrators can take initiatives to es-tablish an effective and well organized layer farming system in Bangladesh. The study also provides useful information to the researchers for further research in this area.